Characteristics, Prehospital Management, and Outcomes in Patients Assessed for Hypoglycemia: Repeat Access to Prehospital or Emergency Care. (4th May 2019) - Sinclair, Julie E.; Austin, Mike; Froats, Mark; Leduc, Shannon; Maloney, Justin; Dionne, Richard; Reed, Andy; Vaillancourt, Christian
Abstract: Background: In Ontario, Canada, there currently are no prehospital treat-and-release protocols and the safety of this practice remains unclear. We sought to describe the characteristics, management, and outcomes of patients with hypoglycemia treated by paramedics, and to determine the predictors of repeat access to prehospital or emergency department (ED) care within 72 hours of initial paramedic assessment.Methods: We performed a health record review of paramedic call reports and ED records over a 12-month period. We queried prehospital databases to identify cases, which included all adult patients (≥ 18 years) with a prehospital glucose reading of <72mg/dl (4.0mmol/L) and excluded terminally ill and cardiac arrest patients. We developed and piloted a standardized data collection tool and obtained consensus on all data definitions before initiation of data extraction by trained investigators. Data analyses include descriptive statistics with standard deviations, Chi-square, t-tests, and logistic regression with adjusted odds ratios (AdjOR).Results: There were 791 patients with the following characteristics: mean age 56.2, male 52.3%, known diabetic 61.6%, on insulin 46.1%, mean initial glucose 50.0 dl/mg (2.8 mmol/L), from home 56.3%. They were treated by an Advanced Care Paramedic 80.1%, received IV D50W 38.0%, IM glucagon 18.3%, PO complex carbs 26.6%, and accepted transport to hospital 69.4%. Of those transported, 134/556 (24.3%) were admitted and 9 (1.6%) died in the ED. Overall, 43 patients (5.4%) had repeat access to prehospital/ED care, among those, 8 (18.6%) were related to hypoglycemia. Patients on insulin were less likely to have repeat access to prehospital/ED care (AdjOR 0.4; 95%CI 0.2–0.9). This was not impacted by initial (or refusal of) transport (AdjOR 1.1; 95%CI 0.5–2.4).Conclusion: Although risk of repeat access to prehospital/ED care for patients with hypoglycemia exists, it was less common among patients taking insulin and was not predicted by an initial refusal of transport.